Aspect in English and Pangasinan verbs a constrastive analysis - Mendoza, Isabel Roxas 1925- (Quezon City University of the Philippines, 1965)
This study is concerned with verbs or verb expressions in predicate position. The morphological constituents and the grammatical meanings of these constituents were considered in the description of the verb structures of Pangasinan and English. Patterns containing the different forms were presented for comparison in identifying the similarities between Pangasinan and English verbs as to aspect markers. In the preparation of instructional materials, language teachers teaching the aspect system of English verbs face problems such as: (1) the use of the past progressive tense; (2) the perfect tense (3) the future tense; and (4) the inchoative aspect.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Pangasinan language -- Verbs